Inuit uqausiqatigiit Inuit languages and dialects - Dorais, Louis-Jacques 1945- (Arctic College, Nunatta Campus, 1990)
This study of the Eskimo and Aleut (or Eskaleut) languages of Alaska, northern Canada and Greenland, defines geographical distribution (including a map) and lists and discusses dialects, phonology, grammar, vocabulary, orthography and present state of the language.